Triolein-based polycation lipid nanocarrier for efficient gene delivery: characteristics and mechanism - Zhang ZW (Dove Medical Press, 2011)
Zhiwen Zhang1,2, Xiaoling Fang1, Junguo Hao1, Yajuan Li1, Xianyi Sha1 1Key Laboratory of Smart Drug Delivery, Ministry of Education and PLA, Department of Pharmaceutics, School of Pharmacy, Fudan University, Shanghai, People’s Republic of China; 2Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai, People’s Republic of China Abstract: We proposed to develop a polycation lipid nanocarrier (PLN) with higher transfection efficiency than our previously described polycation nanostrucutred lipid nanocarrier (PNLC). PLN was composed of triolein, cetylated low-molecular-weight polyethylenimine, and dioleoyl phosphatidylethanolamine. The physicochemical properties of PLN and the PLN/DNA complexes (PDC) were characterized. The in vitro transfection was performed in human lung adenocarcinoma (SPC-A1) cells, and the intracellular mechanism was investigated as well. The measurements indicated that PLN and PDC are homogenous nanometer-sized particles with a positive charge. The transfection efficiency of PDC significantly increased with the content of triolein and was higher than that of PNLC and commercial LipofectamineTM 2000. In particular, the transfection of PLN in the presence of 10% serum was more effective than that in its absence. With the help of specific inhibitors of chlorpromazine and filipin, the clathrin-dependent endocytosis pathway was determined to be the main contributor to the successful transfection mediated by PLN in SPC-A1 cells. The captured images verified that the fluorescent PDC was localized in the lysosomes and nuclei after endocytosis. Thus, PLN represents a novel efficient nonviral gene delivery vector. Keywords: triolein, dioleoyl phosphatidylethanolalmine, polyethylenimine, lipid nanocarrier, mechanism